Avaliação do estresse oxidativo sistêmico em ratos submetidos a fármacos antirreabsortivos para indução de osteonecrose - Torriani, Eva Aguiar Almeida Campos Castro (2023)
Antiresorptive drugs, such as alendronate, denosumab and zoledronic acid, have been used in the treatment of bone diseases (osteoporosis, Paget's disease, multiple myeloma, malignant hypercalcemia), in addition to preventing bone metastases in prostate, breast and lung cancer. The main side effect of prolonged use of these drugs in the oral cavity is osteonecrosis of the jaws, characterized by aseptic necrosis of the gnathic bones due to increased bone density and consequent reduction of local microvascularization, resulting in bone exposure and subsequent secondary infection, a complication of difficult to manage in clinical practice. Aseptic bone necrosis is accompanied by a defensive, non-specific, homeostatic response of the organism to changes called oxidative stress. Oxidative stress occurs when there is an overproduction of reactive oxygen species (ROS) that is not neutralized by an adequate level of antioxidants. The relationship between oxidative stress caused by antiresorptive drugs and the development of osteonecrosis is not yet well established in the literature. Therefore, further studies are needed in order to clarify this relationship and discover new agents that can reduce the side effects of these drugs and consequently interfere with the development of osteonecrosis. The objective of the present study is to evaluate the levels of systemic oxidative stress through the products of lipid peroxidation, in rats submitted to antiresorptive drugs, which were submitted to the osteonecrosis development protocol. With this study we conclude that antiresorptive drugs increase the levels of oxidative stress. In the scoping review, the relationship between the level of oxidative stress and the development of osteonecrosis was evaluated and it was concluded that the higher the level of oxidative stress, the greater the chance of developing osteonecrosis.